Parametric and non-parametric regression methods in identifying an impact of components of advertising on consumers behaviour - Chudzian, Joanna; Chrzanowska, Mariola (Zastosowanie parametrycznych i nieparametrycznych metod regresji w celu określenia wpływu składników reklamy na zachowania konsumentów, 2014)
This paper concerns the application of parametric and non-parametric regression methods in explaining the impact of advertising on consumers on the dairy market. Two specific goals were stated in this research. The first goal was to evaluate the impact of advertising components on its effectiveness operationalized as the AIDA marketing model. The second goal attempted at clustering consumers with respect to the effectiveness of subsequent components of advertising. The former was achieved using the parametric regression model, for the latter the regression tree model was applied. Among the components of advertising, the TV medium and music – factors that strongly attract attention – affects the behaviour of consumers of dairy products the most. Other important revealed factors turn out to be varying in significance depending on the regression method applied.
Ekonometria = Econometrics, 2014, Nr 3 (45), s. 56-70
Keywords: regression method; linear regression; regression tree; advertising; dairy market; metoda regresji; regresja liniowa; drzewo regresyjne; reklama; rynek mleczarski